Usefulness of computed tomography-guided puncture biopsy coupled with rapid on-site evaluation for diagnosis of pulmonary lesions: a systematic review and meta‑analysis - Zhongbao Zhang; Rui Liu; JunLin Li; Kai Zhang; Yuan Li; Xiaoqin Zhang; Sanjay Rastogi (Videosurgery and Other Miniinvasive Techniques)
Introduction: Accurate identification of lung lesions during lung biopsy (LB) surgery can be achieved with the use of computed tomography (CT) guidance. The rapid on-site evaluation (ROSE) method allows for quick assessment of the features, cytomorphological traits, and appropriateness of the obtained tissue samples, and might further accelerate the diagnostic workup.